Incoherent transient radio emission from stellar-mass compact objects in the SKA era - Corbel, S.; Miller-Jones, James; Fender, R.; Gallo, E.; Maccarone, T.; O'brien, T.; Paragi, Z.; Rupen, M.; Rushton, A.; Sabatini, S.; Sivakoff, G.; Strader, J.; et al. (2014)
The universal link between the processes of accretion and ejection leads to the formation of jets and outflows around accreting compact objects. Incoherent synchrotron emission from these outflows can be observed from a wide range of accreting binaries, including black holes, neutron stars, and white dwarfs. Monitoring the evolution of the radio emission during their sporadic outbursts provides important insights into the launching of jets, and, when coupled with the behaviour of the source at shorter wavelengths, probes the underlying connection with the accretion process. Radio observations can also probe the impact of jets/outflows (including other explosive events such as magnetar giant flares) on the ambient medium, quantifying their kinetic feedback. The high sensitivity of the SKA will enabling the monitoring of accreting stellar-mass compact objects from their bright, Eddington-limited outburst states down to the lowest-luminosity quiescent levels, whose intrinsic faintness has to date precluded detailed studies. A census of quiescently accreting black holes will constrain binary evolution processes. By extending existing investigations of black hole jets to the fainter jets from neutron star and white dwarf systems, the SKA will permit comparative studies to determine the role of the compact object in jet formation.Further, the SKA will enable the detection and monitoring of all bright flaring transients in the observable local Universe (within 15 Mpc), including the radio counterparts of ultraluminous X-ray sources, improving our understanding of accretion and jet ejection at the highest rates, with important implications for the growth of the first quasars. As synchrotron events peak earlier at higher frequencies, and with higher flux densities, such studies will be best enabled by SKA1-MID. SKA1-MID will probe isolated quiescent black holes undergoing Bondi-Hoyle accretion from the nearby environment, both stellar-mass black holes in the field and the putative population of intermediate black holes in globular clusters. Detecting the latter would confirm the existence of the black hole seeds that must have existed in the early Universe. This chapter reviews the progress that will be made by the SKA in studying incoherent synchrotron emission from accreting compact objects. We also discuss the potential of the astrometric and imaging observations that would be possible should a significant VLBI component be available for SKA.